IT'S WHAT YOU HAVE, NOT WHAT YOU LOSE: EFFECTS OF RESOURCE ACCUMULATION AND LOSS ON GOAL ORIENTATION ACROSS ADULTHOOD. (11th November 2018) - Gong, X; Freund, A
Abstract: The literature documents a motivational shift in goal orientation such that younger adults focus more on striving for gains than maintenance of functioning or avoidance of losses. With increasing age, adults become more maintenance-oriented and, in old adulthood, more loss-avoidance oriented. This motivational shift might be due to the increasing threat of losses, particularly in old age. Alternatively, it might be the accumulation of resources such as material wealth that leads adults to become more protective of what they have achieved. The current study explored the effects of perceived resource accumulation and (threat of) losses on goal orientation in 16 life domains in N = 174 young, middle-aged, and older adults. These domains were supposed to vary in cumulativeness (resources can be accumulated or not) and threat of losses (resources can be lost or not) to maximize the chance of dissociating the effects of perceived accumulation and (threat of) losses. Based on participants' ratings, 4 of the 16 domains were selected for the subsequent analyses. Results replicated the finding that older adults generally report stronger maintenance and loss-prevention orientation than younger adults. Perceived resource accumulation positively related to maintenance orientation, particularly in old age. Moreover, higher perceived resource accumulation was associated with weaker loss-prevention orientation in young adulthood but stronger loss-prevention orientation in older adults. These findings suggest that resource accumulation may play a crucial role in motivational shifts across adulthood. In contrast, resource loss might play a less important role than previously assumed.